Prevalence, awareness, treatment, control and socio demographic determinants of hypertension in Malaysian adults. (December 2016) - Abdul-Razak, Suraya; Daher, Aqil; Ramli, Anis; Ariffin, Farnaza; Mazapuspavina, Md; Ambigga, Krishnapillai; Miskan, Maizatullifah; Abdul-Hamid, Hasidah; Mat-Nasir, Nafiza; Nor-Ashikin, Mohamed; Ng, Kien Keat; Nawawi, Hapizah; et al.
Abstract Background Hypertension is the leading cardiovascular risk factor globally as well as in Malaysia. This study aimed to estimate the prevalence, awareness, treatment, control and the socio demographic determinants of hypertension among Malaysian adults. Method The analytic sample consisted of 11, 288 adults aged ≥ 30 years recruited at baseline in 2007–2011 from the REDISCOVER Study which is an ongoing, prospective cohort study involving 18 urban and 22 rural communities in Malaysia. Socio-demographics, anti-hypertensive treatment details and an average of at least two blood pressure measurements were obtained. Results The age-adjusted prevalence was 42.0 % (CI: 40.9–43.2) and was higher in men [43.5 % (CI: 41.2–45.0)] than women [41.0 % (CI: 39.8–42.3)]. Participants from rural areas (APR: 1.12, CI: 1.04–1.20); aged at least 40–49 years (APR: 1.86, CI: 1.62–2.14); who were overweight (APR: 1.24, CI: 1.15–1.34) and obese (APR: 1.54, CI: 1.43–1.6) were more likely to have hypertension. The Indigenous ethnic group was less likely to be aware (APR: 0.81, CI: 0.69–0.92) and to be on treatment (APR: 0.66, CI: 0.55–0.79). Those in rural areas were less likely to have their hypertension controlled (APR: 0.61, CI: 0.49–0.75). On the other hand, control was more likely in females (APR: 1.25, CI: 1.01–1.54) and Indigenous group (APR: 1.64, CI: 1.19–2.25). Conclusion Hypertension is common in the Malaysian adults. The control of hypertension has increased over the years but is still quite low. Public health measures, as well as individual interventions in primary care are crucial to reduce their risk of developing complications.